2003
DOI: 10.1034/j.1600-6143.2003.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of 4-1BB in Allograft Rejection Mediated by CD8+ T Cells

Abstract: Blockade of traditional costimulatory molecules fails to inhibit rejection in many models where CD8 + T cells are sufficient to mediate rejection. This observation demonstrates that in many settings CD8 + T cells are not dependent upon CD28 or CD154 signals to mediate rejection. 4-1BB (CD137) has been shown to be an important regulatory molecule for CD8 + T cells in a variety of nontransplant models. Here we show that blocking the 4-1BB pathway significantly inhibited rejection of intestinal allografts by CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 39 publications
6
52
0
Order By: Relevance
“…This difference between T CM and T EM cells is interesting and warrants further investigation. We studied CD8 ϩ , but not CD4 ϩ , memory T cells in this allogeneic setting because: 1) immune regulation in vivo results in a long-lasting CD8 ϩ memory but in a declining CD4 ϩ memory pool over time (54,55), indicating that the CD8 ϩ memory pool may by more important for long-term immunity than is CD4 ϩ memory; 2) memory CD8 ϩ T cells are resistant to the conventional costimulatory blockade (4,7,56) and therefore could function in the absence of chemokines; and 3) memory CD8 ϩ T cells can be generated in response to an alloantigen independently of CD4 ϩ T cell help (16), suggesting that memory CD8 ϩ T cells are independent and may pose a more serious threat to tolerance induction than do their CD4 ϩ counterparts. Our studies demonstrate that the migration and function of T CM , but not T EM , CD8 ϩ cells are impaired in the absence of MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…This difference between T CM and T EM cells is interesting and warrants further investigation. We studied CD8 ϩ , but not CD4 ϩ , memory T cells in this allogeneic setting because: 1) immune regulation in vivo results in a long-lasting CD8 ϩ memory but in a declining CD4 ϩ memory pool over time (54,55), indicating that the CD8 ϩ memory pool may by more important for long-term immunity than is CD4 ϩ memory; 2) memory CD8 ϩ T cells are resistant to the conventional costimulatory blockade (4,7,56) and therefore could function in the absence of chemokines; and 3) memory CD8 ϩ T cells can be generated in response to an alloantigen independently of CD4 ϩ T cell help (16), suggesting that memory CD8 ϩ T cells are independent and may pose a more serious threat to tolerance induction than do their CD4 ϩ counterparts. Our studies demonstrate that the migration and function of T CM , but not T EM , CD8 ϩ cells are impaired in the absence of MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…We studied CD8 ϩ , but not CD4 ϩ , memory T cells in this allogeneic setting because 1) immune regulation in vivo results in a long-lasting CD8 ϩ memory but a declining CD4 ϩ memory pool over time (44,45); 2) memory CD8 ϩ T cells are resistant to the conventional costimulatory blockade (22,23,46) and therefore could be resistant to tryptophan catabolism; and 3) memory CD8 ϩ T cells can be generated in response to an alloantigen independently of CD4 ϩ T cell help (32), suggesting that memory CD8 ϩ T cells are independent and may pose a more serious threat to tolerance induction than their CD4 ϩ counterparts. Our studies demonstrate that memory CD8 ϩ T cells are subject to the regulation mediated by tryptophan catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…We studied CD8+, but not CD4+, memory T cells in this setting because: (1) allospecific CD8+ T cells from transgenic mice are available for tracking in vivo; (2) immune regulation results in a long-lasting CD8+ memory but a declining CD4+ memory pool (48,49) and (3) memory CD8+ T cells are resistant to conventional costimulatory blockade (1,2,50). Our studies identified CD8+ memory and IL-7 as a target to induce long-term allograft survival or tolerance.…”
Section: Discussionmentioning
confidence: 99%